Analisis Kelayakan Usaha lndustri Tempe Skala Rumah Tangga di Kota Banjarbaru - Fauziah Fauziah; Fardianah Mukhyar; Sadik Ikhsan (AGRIDES: Jurnal Agribisnis Perdesaan, 2013)
Tempe is largely consumed by the Indonesian and now become popular across the world. The tempe mdustry has absorb 50% of total soybean consumption in Indonesia. followed by tahu industry (40%) and other soybean based products The tempe consumption in Indonesia ts estimated as much as 6. 45 kg per year. Based these facts. the tempe industry is promising to be developed. Thus, the study is purposed: (1) to explore the tempe business been done on household scale, (2) to calculate the profit and value added of tempe business, and (3) to determine the feasibility of household scale tempe industry in Banjarbaru. By traditional means, the business spent average total cost as many as /DR 24.98 million per month and generated average profit /DR 2.02 million per month. Meanwhlfe, the value added was /DR 8. 19 million per month. The profit rate was 8 09%, higher the inflation level 2. 44%, which mean that the business is feasible.